The Influence of Safety, Health and Work Environment on the Work Productivity of Plastics Division Employees at PT Dragon Product Indonesia - Ardiyanto, Muhamad Aris; Samsuri; Ismartaya (International Journal of Management and Business Intelligence, 2024)
The aim of the research is to analyze and analyze the influence between safety, health, work environment and productivity which can be used as a reference in further research. The method chosen was Explanatory Research. The total sample of employees is 70 people. The research results simultaneously influence all variables on employee productivity. Partially, the variables of work discipline, work motivation and workload influence employee productivity. Safety, health and the work environment each have an important role in increasing employee productivity.